‘There’s always got to be a villain’: the police as ‘dirty’ key workers and the effects on occupational prestige - De Camargo, Camilla (Policing and society, 2022)
The COVID-19 pandemic has afforded the opportunity for key workers in some traditionally ‘dirty’ occupations to experience elevated levels of prestige. Although public perceptions of certain key workers have evolved in this way not all occupations have benefitted from comparable narratives. Using data from 18 police officer interviews, we theorise that the police are constructed as the ‘villains’ of the pandemic, tasked with the ‘dirtier’ responsibilities of enforcing rules that transgress societal order (as opposed to ‘heroes’ performing the more prestigious functions such as saving lives). For this reason, they have not benefitted from the same esteem markers awarded to other key workers, which in turn has had a detrimental effect on their morale. Gratitude, especially experienced via public markers of esteem symbolic of the pandemic, was salient in participants negotiating their ‘dirt’ and occupational prestige.